A TRANSFORMATIONAL LEADERSHIP OF PRIVATE HIGH SCHOOL PRINCIPALS IN MAKASSAR CITY - Arismunandar, Arismunandar; Wahed, Andi; Ervianti, Ervianti; H, Nurhikmah (International Journal of Education, 2023)
This study aims to obtain an overview of the transformational leadership of the head of a private high school in Makassar City. The approach in this study is Quantitative with a descriptive type of research that seeks to describe the four dimensions of transformational leadership of the head of a private high school in Makassar City. In this study, the data collection technique used was a questionnaire that was distributed to 92 samples from 1203 teacher populations who gave assessments to the heads of private high schools in Makassar City. The data analysis technique used in this study is descriptive statistics that only describe the state of the data as it is through parameters such as mean, median, mode, frequency distribution and other statistical measures. The results showed that the transformational leadership of the head of a private high school in Makassar City has (1) a tendency to ideal influence or charisma with a presentation of 77 or 83.16% is in a very high category, (2) inspirational motivational tendencies with presentations of 68.5% are in a very high category, (3) intellectual stimulation tendencies with a percentage of 66.3% are in a very high category,  and (4) the tendency of individual consideration with presentations of 50% is in the high category. Research findings: Principals as transformational leaders can improve response, and commitment, pay attention to the concerns and needs of teachers and employees under them, change the awareness of teachers and employees under them about problems by helping them see problems in new ways, and excite and inspire teachers and employees under them to make extra efforts to achieve school goals. can help teachers and employees to see the positive impact of their work through direct interaction by responding, building commitment and making extra efforts to achieve school goals.